Pertanggungjawaban Debitur Yang Tidak Melaksanakan Kewajibannya Terhadap Kreditur Berdasarkan Perjanjian PKPU (Studi Kasus PT. ST) - Putra, Reval Pradana; Dewi Hariyana, Trinas (WELFARE STATE Jurnal Hukum, 2022)
The objectives to be achieved in this study are to examine and analyze the problems that occur between debtors, namely the old PT. ST owners and their employees where the employees who claim their rights to the new PT. ST owners who should be in the agreement are not the ones who have to bear the burden of the old debtors. . The approach method used is empirical or direct research to related parties. From the responsibilities carried out by the old debtor, he only carried out part of his responsibilities before the payment of the new debtor was completed, after the repayment of the old debtor, the old debtor defaulted by running away from his responsibility to his creditor which was then indirectly transferred to the debtor. the old one is the new owner of PT. ST. Efforts made by the creditor when there is a default by the debtor can be done by litigation or non-litigation starting from subpoenas and so on. Efforts made by creditors against new debtors are carried out in a non-litigation way by paying the installment system with the agreement that has been agreed in the PKPU agreement.